Mama Loundry: Optimizing Mobile Based Administration Processes for Laundry Businesses - Fadhlirrahman Baso; Fariz Ramlan; Tessa` Labennu; Indah Febriyani Asril; Hartini Ramli (Journal of Embedded Systems, Security and Intelligent Systems, 2023)
The laundry application is a mobile application that acts as a service provider resource to its customers. This application is a mobile application and therefore it was developed to facilitate the handling of user problems that are often faced by system administrators, such as: facilitating administrative processes via a smartphone without using a computer because we know that computers are relatively very expensive and consume a lot of electricity. This application is equipped with functions such as order management, customer management and order history. The method used is the SDLC model prototyping method used to quickly gather specific information about user information requirements. Keywords: laundry, app, mobile, android studio, java